2017
DOI: 10.1111/j.1475-5890.2017.12141
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Discharges and Hospital Type: Evidence from the English NHS

Abstract: Delayed discharges of patients from hospital, commonly known as bedblocking, are a long-standing policy concern. Delays can increase the overall cost of treatment and may worsen patient outcomes. We investigate how delayed discharges vary by hospital type (Acute, Specialist, Mental Health, Teaching) and the extent to which such differences can be explained by demography, case mix, hospital quality, the availability of long-term care, and hospital governance as reflected in whether the hospital has Foundation T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 13 publications
2
31
0
Order By: Relevance
“…This is the first systematic review of the literature to take a comprehensive perspective on the impact of delayed discharge on patients, staff, and hospitals; and of their interrelationships . For patients, the main adverse outcomes are an association with an increased risk of mortality, hospital‐acquired infections, mental ill health and reductions in patients’ mobility and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first systematic review of the literature to take a comprehensive perspective on the impact of delayed discharge on patients, staff, and hospitals; and of their interrelationships . For patients, the main adverse outcomes are an association with an increased risk of mortality, hospital‐acquired infections, mental ill health and reductions in patients’ mobility and activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed discharge is an important problem for health‐care providers internationally . It is defined as the period of continued hospital stay after a patient is deemed medically fit to leave hospital but is unable to do so for non‐medical reasons .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discharge delay has been shown to be influenced by socioeconomic and policy factors as well as decision-making process between interdisciplinary team members and patients [ 20 ]. A study by Gaughan et al [ 21 ] has indicated that fewer delayed discharges were associated with hospitals with Foundation Trust status (semi-autonomous organisational units within the NHS in England which have a degree of independence from the Department of Health to decide locally how to meet their obligations) and a greater local provision of long-term care home beds. Analysis of clinical data such as those collected by clinical audits or registry-based clinical trials is an integral part of the delivery of care quality to identify and address factors associated with readmissions [ 22 ] and prolonged LOS [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“… James Gaughan, Hugh Gravelle and Luigi Siciliani investigate whether delayed discharges of patients from hospital, commonly known as bed‐blocking, vary by hospital type. They find that hospitals in England with Foundation Trust status, which gives them greater financial autonomy and flexibility, have fewer delayed discharges.…”
Section: How Important Are the Incentives In The Organisation Of Healmentioning
confidence: 99%